A manganese-based tunnel composite positive electrode material and its preparation method and application
By adopting a manganese base tunnel composite structure in the sodium ion battery positive electrode material to adjust the sodium element content and calcining temperature, the problem of taking into account the rapid sodium ion transmission and long-term stability of the sodium ion battery positive electrode material is solved, and a comprehensive performance of high specific capacity, excellent rate performance and low cost are achieved.
Patent Information
- Application Number
- CN202310115183.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-15
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-02-15
AI Technical Summary
The existing sodium ion battery positive electrode materials are difficult to balance the rapid sodium ion transport and long-term stability, and the single-phase manganese-based oxide materials are difficult to achieve excellent comprehensive performance.
A manganese base tunnel composite cathode material is used, and its chemical formula is aNa0.44MnO2/bNa0.70MnO2, where a+b=1, the ratio of the layered phase and the tunnel phase is adjusted by appropriately adjusting the sodium content and the segmented calcining temperature to form a layered tunnel composite structure.
It achieves the improvement of specific capacity while maintaining cycle stability, has excellent rate performance and air stability, simplifies the material preparation process, reduces costs, and is suitable for large-scale industrial production.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage materials, and in particular to a manganese-based tunnel composite positive electrode material and a preparation method and application thereof. Background Art
[0002] As the demand for renewable green energy continues to increase, new power generation technologies such as wind power and solar power are gradually being widely used across the country. However, their power generation characteristics that rely on the natural environment and weather conditions pose challenges to the overall stability of the power grid system. Therefore, it is imperative to seek high-efficiency, large-scale energy storage technologies for such power generation facilities. Sodium-ion batteries (SIBs) have obvious advantages in terms of mineral resources and costs, and are expected to be used in large-scale energy storage. However, due to the large radius of sodium ions, a practical challenge is how to construct a suitable electrode structure to simultaneously achieve rapid sodium ion transmission and ensure the long-term stability of the structure. Secondly, the positive electrode material accounts for a large proportion of the battery, which plays an important role in improving the overall energy density and cycle life of the battery, and will determine the overall performance of the battery product. Therefore, finding a suitable positive electrode material is urgent.
[0003] As active materials for the positive electrode of sodium-ion batteries, manganese-based oxides have significant advantages in terms of cost, performance and environment. For example, P2-type layered oxides among layered manganese-based oxides have attracted the attention of researchers, mainly due to the + Occupies open triangular prism sites, with a theoretical specific capacity of 170 mAh g -1 . However, during the charge and discharge process, the crystal structure of the material will undergo irreversible destruction and harmful phase transformation under high pressure, resulting in poor cycle stability of the active material, which seriously hinders the commercialization process. Tunnel-type manganese-based oxides show excellent rate performance and cycle stability, but their theoretical specific capacity is low. Therefore, due to the inherent characteristics of the material, it is difficult for single-phase manganese-based oxide positive electrode materials to achieve excellent comprehensive performance.
[0004] Based on the above discussion, relevant researchers have proposed to construct a two-phase composite structure to effectively combine the advantages of the two phases to balance their inherent defects. Common technical means include introducing one or more element doping or changing the calcination temperature to regulate the ratio of the two phases. However, the introduction of other elements will increase the cost of the material, and the specific mechanism also needs further exploration. Secondly, most current research focuses are still on how to improve the specific capacity, but ignores the rate performance and long-cycle stability. Therefore, it is necessary to further develop a layer-tunnel composite positive electrode with low cost, high cycle stability and excellent rate performance. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and to provide a manganese-based tunnel composite positive electrode material and a preparation method and application thereof.
[0006] In order to solve the above technical problems, one of the technical solutions provided by the present invention is as follows:
[0007] A manganese-based tunnel composite positive electrode material, the chemical formula of which is aNa 0.44 MnO2 / bNa 0.70 MnO2, where a+b=1.
[0008] In a more preferred embodiment, a is 0.78-0.82, and b is 0.22-0.18.
[0009] The second technical solution provided by the present invention is as follows:
[0010] A method for preparing the manganese-based tunnel composite positive electrode material as described above comprises the following steps:
[0011] ball-milling appropriate amounts of sodium source and manganese source to obtain precursor powder;
[0012] Pressing the precursor powder into a shape to obtain a precursor block;
[0013] The precursor block is synthesized by a high temperature solid phase method to obtain a manganese-based tunnel composite positive electrode material;
[0014] The atomic weight ratio of the sodium element to the manganese element in the sodium source and the manganese source is 0.44-0.7.
[0015] In a more preferred embodiment, the atomic weight ratio of the sodium element to the manganese element is 0.5-0.6.
[0016] In a more preferred embodiment, the atomic weight ratio of the sodium element to the manganese element is 0.5.
[0017] In a more preferred embodiment, the high temperature solid phase method is to calcine the precursor block in an air atmosphere at 75-925° C. for 28-32 hours.
[0018] In a more preferred embodiment, the high temperature solid phase method is to calcine the precursor block in an air atmosphere at a first temperature, a second temperature and a third temperature for a first period of time, a second period of time and a third period of time respectively;
[0019] The first temperature is less than the second temperature and less than the third temperature;
[0020] The third time period is greater than the first time period and greater than the second time period;
[0021] Wherein, the first temperature, the second temperature and the third temperature are in the range of 75-925°C;
[0022] The total time of the first period, the second period and the third period is within the range of 28-32 hours;
[0023] The first time period and the third time period are both greater than or equal to at least twice the second time period.
[0024] In a more preferred embodiment, the temperature is 75-125°C, the second temperature is 375-425°C, and the third temperature is 875-925°C;
[0025] The first time period is from 11 to 13 hours, the second time period is from 4.5 to 5.5 hours, and the third time period is from 14 to 16 hours.
[0026] In a more preferred embodiment, the sodium source is selected from one or more of sodium acetate, sodium carbonate and sodium hydroxide.
[0027] In a more preferred embodiment, the manganese source is selected from one or more of manganese acetate, manganese carbonate and manganese trioxide.
[0028] In a more preferred embodiment, the pressing molding is to press the precursor powder into a precursor block under a pressure of 5-10 MPa.
[0029] In a more preferred embodiment, the precursor block is in the shape of a cylinder.
[0030] The third technical solution provided by the present invention is as follows:
[0031] A positive electrode plate for a sodium ion battery, wherein the positive electrode plate raw material comprises the manganese-based tunnel composite positive electrode material as described above, a conductive additive, a binder and a current collector.
[0032] The fourth technical solution provided by the present invention is as follows:
[0033] A sodium ion battery, comprising the manganese-based tunnel composite positive electrode material as described above.
[0034] In summary, the present application includes at least one of the following beneficial technical effects:
[0035] 1. A layer-tunnel composite cathode material with excellent rate performance is obtained by appropriately adjusting the sodium content. Under the synergistic effect of the two phases, the phase transition and volume change of the material are effectively suppressed, and the specific capacity can be improved while maintaining the cycle stability. In addition, the layer-tunnel composite cathode material has good air stability and has certain commercial prospects. The cathode material prepared by the present invention has excellent cycle performance, power density and energy density.
[0036] 2. A layer-tunnel composite positive electrode material with excellent performance was prepared without introducing other elements or complicated processes, thereby simplifying the complexity of material preparation and reducing production costs. At the same time, the process is simple and has little impact on the environment, making it suitable for large-scale industrial production and application.
[0037] Other features and beneficial effects of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other beneficial effects of the present invention can be realized and obtained by the structures particularly pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. The positional relationships described in the drawings in the following description are based on the directions in which the components are drawn in the diagrams, unless otherwise specified.
[0039] Figure 1 0.80Na of Example 1 of the present invention 0.44 MnO2 / 0.20Na 0.70 MnO2 (80T / 20L), 0.75Na of Example 2 0.44 MnO2 / 0.25Na 0.70 MnO2 (75T / 25L) and 0.34Na of Example 3 0.44 MnO2 / 0.66Na 0.70 MnO2 (34T / 66L) composite material and Na 0.44 MnO2 (100T) and Na 0.70 X-ray diffraction patterns of respective MnO2(100L) materials.
[0040] Figure 2 This is a field emission scanning electron microscope image of the 80T / 20L composite material obtained in Example 1 of the present invention.
[0041] Figure 3 This is a transmission electron microscope image of the 80T / 20L composite material in Example 1 of the present invention.
[0042] Figure 4 This is a rate performance diagram of sodium ion half-cells assembled using the 80T / 20L, 34T / 66L composite materials of Examples 1 and 3 of the present invention and the 100T, 100L of Comparative Examples 1 and 2 as positive electrode materials.
[0043] Figure 5 This is a long cycle performance diagram of sodium ion half-cells assembled using 80T / 20L, 75T / 25L, 34T / 66L composite materials of Examples 1, 2, and 3 of the present invention and 100T and 100L of Comparative Examples 1 and 2 as positive electrode materials. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; the technical features designed in different implementation modes of the present invention described below can be combined with each other as long as they do not conflict with each other; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0045] In the description of the present invention, it should be noted that all terms used in the present invention (including technical terms and scientific terms) have the same meanings as those generally understood by ordinary technicians in the field to which the present invention belongs, and cannot be understood as limiting the present invention; it should be further understood that the terms used in the present invention should be understood to have the same meanings as these terms in the context of this specification and in the relevant fields, and should not be understood in an idealized or overly formal sense, unless explicitly defined in the present invention.
[0046] The present invention provides a low-cost manganese-based tunnel composite sodium ion battery positive electrode material with high rate performance, aiming to improve the defects of existing single-phase materials and solve the problems of low rate performance and poor cycle stability of current tunnel composite materials.
[0047] An embodiment of the present invention provides a manganese-based tunnel composite positive electrode material, whose chemical formula is aNa 0.44 MnO2 / bNa 0.70 MnO2, where a+b=1.
[0048] In one or more preferred embodiments, a is 0.78-0.82, wherein a can be 0.78, 0.79, 0.80, 0.81, 0.82, or any point value between the two including 0.80, and b is 0.18-0.22, wherein b can be 0.18, 0.19, 0.20, 0.21, 0.22, or any point value between the two including 0.20; preferably, a is 0.80 and b is 0.20; in the present invention, by combining a small amount of layered structure and tunnel structure, the specific capacity can be effectively improved on the basis of ensuring the cycle stability, thereby ensuring that the battery has excellent comprehensive performance, and when there are too many layered structures, the cycle stability will be greatly reduced, thereby affecting its comprehensive performance.
[0049] With respect to the manganese-based tunnel composite positive electrode material provided in the above embodiment, the present invention provides a method for preparing the manganese-based tunnel composite positive electrode material as described in the above embodiment, comprising the following steps:
[0050] ball-milling appropriate amounts of sodium source and manganese source to obtain precursor powder;
[0051] In one or more examples, the sodium source is selected from one or more of sodium acetate, sodium carbonate and sodium hydroxide.
[0052] In one or more examples, the manganese source is selected from one or more of manganese acetate, manganese carbonate, and manganese trioxide.
[0053] It is worth noting that the present invention specifically selects compounds containing C, H, and O in the chemical formula. One reason is that the compounds formed by these elements will decompose during the high-temperature calcination process and will not cause pollution to the material. Different materials will have a certain impact on the structure and electrochemical properties of the final material. In particular, the performance of the layer-tunnel composite positive electrode material prepared by selecting sodium acetate as the sodium source in the example is more excellent.
[0054] Pressing the precursor powder into a shape to obtain a precursor block;
[0055] In one or more examples, the pressing molding is to press the precursor powder into a precursor block under a pressure of 5-10MPa. In the present invention, the pressing molding is performed within this pressure range, so that more sodium ions can enter the crystal lattice during the high-temperature reaction of the material, which is beneficial to the crystallinity and purity of the material. If the pressure is too high or too low, it will affect the crystallinity of the final composite material to a certain extent.
[0056] In one or more examples, the shape of the precursor block is a cylinder. Of course, in one or more examples of the present invention, the shape of the precursor block may also be other shapes, such as a cuboid, a cube, and the like.
[0057] The precursor block is synthesized by a high temperature solid phase method to obtain a manganese-based tunnel composite positive electrode material;
[0058] In one or more examples, the high temperature solid phase method is to calcine the precursor block in an air atmosphere at 100-900° C. for 28-32 hours;
[0059] Preferably, the high temperature solid phase method is to calcine the precursor block in an air atmosphere at a first temperature, a second temperature and a third temperature for a first period of time, a second period of time and a third period of time respectively;
[0060] The first temperature is less than the second temperature and less than the third temperature;
[0061] The third time period is greater than the first time period and greater than the second time period;
[0062] Wherein, the first temperature, the second temperature and the third temperature are in the range of 75-925°C;
[0063] The total time of the first period, the second period and the third period is within the range of 28-32 hours;
[0064] The first time period and the third time period are both greater than or equal to at least twice the second time period.
[0065] More preferably, the temperature is 75-125°C, the second temperature is 375-425°C, and the third temperature is 875-925°C;
[0066] The first time period is from 11 to 13 hours, the second time period is from 4.5 to 5.5 hours, and the third time period is from 14 to 16 hours.
[0067] The high temperature solid phase method adopts different temperatures in order to stably form two structures, wherein lower temperatures, such as 375-425°C, especially in the range of 390-410°C approaching 400°C, will be more conducive to the formation of tunnel-type structures, while higher temperatures, such as 875-925°C, especially in the range of 890-910°C approaching 900°C, will be more conducive to the formation of layered structures. At the same time, long-term treatment at this temperature can form highly crystalline and dual-phase composite materials. This temperature range can ensure the stable formation of the two structures.
[0068] Among them, the atomic stoichiometric ratio of sodium element to manganese element contained in the sodium source and the manganese source is 0.44-0.7, preferably, the atomic stoichiometric ratio is 0.5-0.6, and more preferably, the atomic stoichiometric ratio is 0.5; based on the above, the inventors found in the experimental process that only when the atomic stoichiometric ratio of sodium element to manganese element is within this range can the material of the layer-tunnel composite structure be synthesized, and it has excellent comprehensive electrochemical properties, rather than outstanding performance in a single property.
[0069] The technical solution of the present invention is further illustrated and described below through specific embodiments, but the protection scope of the present invention is not limited thereto.
[0070] Example 1
[0071] In this embodiment, a manganese-based tunnel composite positive electrode material 0.80Na 0.44 MnO2 / 0.20Na 0.70 Taking MnO2 (80T / 20L) as an example, where T refers to tunnel type and L refers to layered, the manganese-based tunnel composite positive electrode material is used as the active material of the positive electrode sheet for the preparation of sodium ion batteries, which specifically includes the following steps:
[0072] 1) Preparation of manganese-based tunnel composite positive electrode materials.
[0073] 0.05mol NaCH3COO and 0.1mol Mn(CH3COO)2 were placed in a ball mill and mixed uniformly at a speed of 350 rpm for 2.5 hours. The uniform precursor powder obtained by ball milling was pressed into a flat cylindrical block with a diameter of 9mm under a certain pressure (5-10MPa); the precursor block was placed in a crucible and transferred to a muffle furnace for high-temperature calcination. Heat treatment was performed at 100℃-12h, 400℃-5h and 900℃-15h in an air atmosphere. After cooling to room temperature with the furnace, grinding was performed to obtain a black powder manganese-based tunnel composite positive electrode material 80T / 20L. Its XRD spectrum is shown in Figure 1 ,From the XRD spectrum, the crystal structure of 80T / 20L is a layer-tunnel composite structure. Figure 2 The scanning electron microscope (SEM) image of 80T / 20L shows that the composite structure has two different types of morphology, corresponding to two different structures, namely, layered structure and tunnel structure. Figure 3 This is the transmission electron microscope (TEM) image of 80T / 20L, which also corresponds to two different structures.
[0074] 2) Preparation of positive electrode
[0075] The prepared 80T / 20L powder was mixed with acetylene black and binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) solvent was added. The mixture was ground in a room temperature dry environment to form a slurry, and then the slurry was evenly coated on the current collector aluminum foil and dried under an infrared lamp before being cut into (12×12) mm 2 The electrode was dried at 60°C for 12 hours under vacuum conditions and then transferred to a glove box for use.
[0076] 3) Preparation of sodium ion batteries
[0077] The sodium ion battery was assembled in an Ar atmosphere glove box, using sodium metal as the negative electrode and NaClO4 / propylene carbonate (PC) solution as the electrolyte to assemble a CR2032 button cell. The constant current charge and discharge mode was used, and the first test was the rate performance, with the charge cut-off voltage of 4.0V and the discharge cut-off voltage of 1.5V, respectively, at 0.1Ag -1 , 0.2Ag -1 , 0.5Ag -1 , 1Ag -1 , 2Ag -1 , 4Ag -1 and 0.1Ag -1 The charge and discharge test was carried out at a current density of Figure 4 , 80T / 20L positive electrode in 4Ag -1 It can still provide 87mAhg at a high current density -1 The high specific capacity has excellent rate performance. -1 A long cycle test of 200 cycles was carried out under the conditions of a current density of 4.3V for charging and a cut-off voltage of 1.5V for discharging. The test results are as follows Figure 5 , the capacity retention rate can reach more than 85%, further proving that the long-cycle performance of the material can be effectively enhanced at this ratio.
[0078] Example 2
[0079] In this embodiment, a manganese-based tunnel composite positive electrode material 0.75Na 0.44 MnO2 / 0.25Na 0.70 Taking MnO2 (75T / 25L) as an example, where T refers to tunnel type and L refers to layered, the manganese-based tunnel composite positive electrode material is used as the active material of the positive electrode sheet for the preparation of sodium ion batteries, which specifically includes the following steps:
[0080] 1) Preparation of manganese-based tunnel composite positive electrode materials.
[0081] 0.055 mol NaCH3COO and 0.1 mol Mn(CH3COO)2 were placed in a ball mill and mixed uniformly at a speed of 350 rpm for 2.5 hours. The uniform precursor powder obtained by ball milling was pressed into a flat cylindrical block with a diameter of 9 mm under a certain pressure (5-10 MPa); the precursor block was placed in a crucible and transferred to a muffle furnace for high-temperature calcination. Heat treatment was performed at 100℃-12h, 400℃-5h and 900℃-15h in an air atmosphere. After cooling to room temperature with the furnace, grinding was performed to obtain a black powder manganese-based tunnel composite positive electrode material 75T / 25L. Its XRD spectrum is shown in Figure 1,From the XRD spectrum, the crystal structure of 75T / 25L is a layer-tunnel composite structure.
[0082] 2) Preparation of positive electrode
[0083] The prepared 75T / 25L powder was mixed with acetylene black and binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) solvent was added. The mixture was ground in a room temperature dry environment to form a slurry, and then the slurry was evenly coated on the current collector aluminum foil and dried under an infrared lamp before being cut into (12×12) mm 2 The electrode was dried at 60°C for 12 hours under vacuum conditions and then transferred to a glove box for use.
[0084] 3) Preparation of sodium ion batteries
[0085] The sodium ion battery was assembled in an Ar atmosphere glove box, using sodium metal as the negative electrode and NaClO4 / propylene carbonate (PC) solution as the electrolyte to form a CR2032 button cell. The constant current charge and discharge mode was used at 0.17Ag -1 A long cycle test of 200 cycles was carried out under the conditions of a current density of 4.3V for charging and a cut-off voltage of 1.5V for discharging. The test results are as follows Figure 5 , the capacity retention rate can reach 80%.
[0086] Example 3
[0087] In this embodiment, a manganese-based tunnel composite positive electrode material 0.34Na 0.44 MnO2 / 0.66Na 0.70 MnO2 (34T / 66L), where T refers to tunnel type and L refers to layered. The manganese-based tunnel composite positive electrode material is used as the active material of the positive electrode sheet for the preparation of a sodium ion battery, which specifically includes the following steps:
[0088] 1) Preparation of manganese-based tunnel composite cathode materials
[0089] 0.06mol NaCH3COO and 0.1mol Mn(CH3COO)2 were placed in a ball mill and mixed uniformly at a speed of 350 rpm for 2.5 hours. The uniform precursor powder obtained by ball milling was pressed into a flat cylindrical block with a diameter of 9mm under a certain pressure (5-10MPa); the precursor block was placed in a crucible and transferred to a muffle furnace for high-temperature calcination. Heat treatment was performed at 100℃-12h, 400℃-5h and 900℃-15h in an air atmosphere. After cooling to room temperature with the furnace, grinding was performed to obtain a black powder manganese-based tunnel composite positive electrode material 34T / 66L. Its XRD spectrum is shown in Figure 1,From the XRD spectrum, the crystal structure of 34T / 66L is a layer-tunnel composite structure.
[0090] 2) Preparation of positive electrode
[0091] The prepared 80T / 20L powder was mixed with acetylene black and binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) solvent was added. The mixture was ground in a room temperature dry environment to form a slurry, and then the slurry was evenly coated on the current collector aluminum foil and dried under an infrared lamp before being cut into (12×12) mm 2 The electrode was dried at 60°C for 12 hours under vacuum conditions and then transferred to a glove box for use.
[0092] 3) Preparation of sodium ion batteries
[0093] The sodium ion battery was assembled in an Ar atmosphere glove box, using sodium metal as the negative electrode and NaClO4 / propylene carbonate (PC) solution as the electrolyte to assemble a CR2032 button cell. The constant current charge and discharge mode was used, and the rate performance was tested first, with a charge cut-off voltage of 4.0V and a discharge cut-off voltage of 1.5V, and at 0.1Ag -1 , 0.2Ag -1 , 0.5Ag -1 , 1Ag -1 , 2Ag -1 , 4Ag -1 and 0.1Ag -1 The charge and discharge test was carried out at a current density of Figure 4 Since the layered structure in the 34T / 66L cathode accounts for a large proportion, the 4Ag -1 The specific capacity is only 40 mAh g at high current density. -1 The second is at 0.17Ag -1 A long cycle test of 200 cycles was carried out under the conditions of a current density of 1.5V, a charge cut-off voltage of 4.3V, and a discharge cut-off voltage of 1.5V. The test results are as follows Figure 5 , the capacity retention is only 34%, indicating that although the initial specific capacity is high at this ratio, the cycle stability is poor.
[0094] Comparative Example 1
[0095] This comparative example uses a single tunnel-type positive electrode material Na 0.44 Taking MnO2(100T) as an example, where T refers to tunnel type, the single tunnel type positive electrode material is used as the active material of the positive electrode sheet for the preparation of sodium ion batteries, which specifically includes the following steps:
[0096] 1) Preparation of tunnel-type structured positive electrode materials.
[0097] 0.044 mol NaCH3COO and 0.1 mol Mn(CH3COO)2 were placed in a ball mill and mixed uniformly at a speed of 350 rpm for 2.5 hours. The uniform precursor powder obtained by ball milling was pressed into a flat cylindrical block with a diameter of 9 mm under a certain pressure (5-10 MPa); the precursor block was placed in a crucible and transferred to a muffle furnace for high-temperature calcination. Heat treatment was performed at 100℃-12h, 400℃-5h and 900℃-15h in an air atmosphere. After cooling to room temperature with the furnace, grinding was performed to obtain a black powder manganese-based tunnel composite positive electrode material 100T, and its XRD spectrum can be found in Figure 1 ,From the XRD pattern, the crystal structure of 100T is a single tunnel structure.
[0098] 2) Preparation of positive electrode
[0099] The prepared 100T powder was mixed with acetylene black and binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) solvent was added. The mixture was ground in a dry environment at room temperature to form a slurry. The slurry was then evenly coated on the current collector aluminum foil and dried under an infrared lamp before being cut into (12×12) mm 2 The electrode was dried at 60°C for 12 hours under vacuum conditions and then transferred to a glove box for use.
[0100] 3) Preparation of sodium ion batteries
[0101] The sodium ion battery was assembled in an Ar atmosphere glove box, using sodium metal as the negative electrode and NaClO4 / propylene carbonate (PC) solution as the electrolyte to assemble a CR2032 button cell. The constant current charge and discharge mode was used, and the first test was the rate performance, with the charge cut-off voltage of 4.0V and the discharge cut-off voltage of 1.5V, respectively, at 0.1Ag -1 , 0.2Ag -1 , 0.5Ag -1 , 1Ag -1 , 2Ag -1 , 4Ag -1 and 0.1Ag -1 The charge and discharge test was carried out at a current density of Figure 4 , 100T positive electrode has better stability, but in 4Ag -1 The specific capacity is only 59 mAh g -1 The second is at 0.17Ag -1 A long cycle test of 200 cycles was carried out under the conditions of a current density of 4.3V for charging and a cut-off voltage of 1.5V for discharging. The test results are as follows Figure 5 , although the capacity retention rate can reach more than 85%, the capacity is lower than 80T / 20L.
[0102] Comparative Example 2
[0103] In this comparative example, a single P2-type layered positive electrode material Na 0.70 Taking MnO2(100L) as an example, where L refers to the tunnel type, the single P2-type layered structure positive electrode material is used as the active material of the positive electrode sheet for the preparation of a sodium ion battery, which specifically includes the following steps:
[0104] 1) Preparation of P2 type layered structure positive electrode materials.
[0105] 0.07 mol NaCH3COO and 0.1 mol Mn(CH3COO)2 were placed in a ball mill and mixed uniformly at a speed of 350 rpm for 2.5 hours. The uniform precursor powder obtained by ball milling was pressed into a flat cylindrical block with a diameter of 9 mm under a certain pressure (5-10 MPa); the precursor block was placed in a crucible and transferred to a muffle furnace for high-temperature calcination. Heat treatment was performed at 100℃-12h, 400℃-5h and 900℃-15h in an air atmosphere. After cooling to room temperature with the furnace, grinding was performed to obtain a black powder manganese-based tunnel composite positive electrode material 100L, and its XRD spectrum can be found in Figure 1 ,From the XRD pattern, the crystal structure of 100T is a single tunnel structure.
[0106] 2) Preparation of positive electrode
[0107] The prepared 100T powder was mixed with acetylene black and binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) solvent was added. The mixture was ground in a dry environment at room temperature to form a slurry. The slurry was then evenly coated on the current collector aluminum foil and dried under an infrared lamp before being cut into (12×12) mm 2 The electrode was dried at 60°C for 12 hours under vacuum conditions and then transferred to a glove box for use.
[0108] 3) Preparation of sodium ion batteries
[0109] The sodium ion battery was assembled in an Ar atmosphere glove box, using sodium metal as the negative electrode and NaClO4 / propylene carbonate (PC) solution as the electrolyte to assemble a CR2032 button cell. The constant current charge and discharge mode was used, and the first test was the rate performance, with the charge cut-off voltage of 4.0V and the discharge cut-off voltage of 1.5V, respectively, at 0.1Ag -1 , 0.2Ag -1 , 0.5Ag -1 , 1Ag-1 , 2Ag -1 , 4Ag -1 and 0.1Ag -1 The charge and discharge test was carried out at a current density of Figure 4 Although the initial specific capacity of 100L is high, the cycle stability is poor. -1 The specific capacity is only 36 mAhg at a current density of -1 The second is at 0.17Ag -1 A long cycle test of 200 cycles was carried out under the conditions of a current density of 4.3V for charging and a cut-off voltage of 1.5V for discharging. The test results are as follows Figure 5 It can be seen that after 120 cycles, the capacity shows a cliff-like downward trend.
[0110] It should be noted that the specific parameters or some commonly used reagents in the above embodiments are specific embodiments or preferred embodiments of the present invention, rather than limiting them; those skilled in the art can make adaptive adjustments within the scope of the present invention. In addition, unless otherwise specified, the raw materials used can also be conventional commercial products in the art, or prepared by conventional methods in the art.
[0111] In summary, compared with the prior art, the low-cost manganese-based tunnel composite positive electrode material with high rate performance provided by the embodiment of the present invention can be used for the positive electrode plate of a sodium ion battery. The manganese-based tunnel composite positive electrode material adjusts the ratio of the P2-type layered phase and the tunnel phase by appropriately adjusting the stoichiometry of sodium and the staged calcination temperature. The synergistic effect of the layer-tunnel two phases effectively improves the cycle stability and specific capacity. Since the tunnel phase accounts for a large proportion, the effect is particularly significant in rate performance, thereby achieving more excellent comprehensive performance. The positive electrode material prepared by the present invention has high power density, cycle stability and energy density.
[0112] In addition, those skilled in the art should understand that, although there are many problems in the prior art, each embodiment or technical solution of the present invention can be improved in only one or several aspects, without having to solve all the technical problems listed in the prior art or background technology at the same time. Those skilled in the art should understand that the content not mentioned in a claim should not be used as a limitation on the claim.
[0113] Although the terms such as sodium source, manganese source, precursor powder, precursor block, ball milling, pressing and molding are used more frequently in this article, the possibility of using other terms is not excluded. These terms are used only to more conveniently describe and explain the essence of the present invention; interpreting them as any additional restrictions is contrary to the spirit of the present invention; the terms "first", "second", etc. (if any) in the description and claims of the embodiments of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence.
[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A manganese-based tunnel composite positive electrode material, characterized in that: Its general chemical formula is aNa 0.44 MnO2 / bNa 0.70 MnO2, wherein a+b=1, and its preparation method comprises the following steps: ball-milling appropriate amounts of sodium source and manganese source to obtain precursor powder; Pressing the precursor powder into a shape to obtain a precursor block; The precursor block is synthesized by a high temperature solid phase method to obtain a manganese-based tunnel composite positive electrode material; Wherein, the atomic stoichiometric ratio of the sodium element to the manganese element contained in the sodium source and the manganese source is 0.44-0.70; The high temperature solid phase method is to calcine the precursor block in an air atmosphere at a first temperature, a second temperature and a third temperature for a first period, a second period and a third period respectively; The temperature is 75-125°C, the second temperature is 375-425°C, and the third temperature is 875-925°C; The first time period is 11-13 hours, the second time period is 4.5-5.5 hours, and the third time period is 14-16 hours.
2. The manganese-based tunnel composite positive electrode material according to claim 1, characterized in that: The sodium source is selected from one or more of sodium acetate, sodium carbonate and sodium hydroxide.
3. The manganese-based tunnel composite positive electrode material according to claim 1, characterized in that: The manganese source is selected from one or more of manganese acetate, manganese carbonate and manganese trioxide.
4. The manganese-based tunnel composite positive electrode material according to claim 1, characterized in that: The pressing molding is to press the precursor powder into a precursor block under a pressure of 5-10 MPa.
5. A positive electrode plate for a sodium ion battery, characterized in that: The raw materials of the positive electrode plate include the manganese-based tunnel composite positive electrode material as claimed in claim 1, a conductive additive, a binder and a current collector.
6. A sodium ion battery, characterized in that: The sodium ion battery comprises the manganese-based tunnel composite positive electrode material as claimed in claim 1.